Produção, qualidade e decomposição de papuã sob intensidades de pastejo e níveis de nitrogênio - Adami, Paulo Fernando (2009)
Grazing intensity and nitrogen fertilization levels have a major influence over the success of the soil-plant-animal system once they influence directly the vegetable and animal production and also the nutrient cycling. Understand how this factors are related help making the decision about the management to be used to improve the use of natural resources. Following this idea, an experiment was developed at the Agronomist institute of Paraná (IAPAR), experimental unit of Pato Branco with the aim to evaluate the influence of different management over the dynamic of Brachiaria plantaginea forage. The experiment was laid out as random block design with six treatments and two replications. Treatments consisted of a combination of two factors (3 x 2). The factor A refers to the levels of nitrogen (0, 200 and 400 kg of N.ha-1 using urea) and factor D refers to the grazing intensities being the low forage mass (LM) wanted in 1.500 kg of DM.ha-1 and the high forage mass (HM) in 3.000 kg of DM.ha-1 with a continuous stocking rate. Were used goats half blood Boer with five months old and average life weight of 21 kg to adjust the wanted forage mass. The real forage mass, the average plant height and the animal livestock at the different grazing intensities were 2.567 and 3.862 kg.ha-1 of DM; 23.6 e 31.2cm and 2.804 and 2.089 kg of LW.ha-1 to the LM and HM respectively. The FA showed data of 100, 147 and 132 kg of DM.ha-1.day-1, and the total production was 13.659, 19.834 and 17.820 kg of DM.ha-1 respectively to the 0, 200 and 400 kg of N.ha-1. The vegetable dry matter decomposition rate was higher than the animal manure and the constant of decomposition showed a tendency to increase as the level of N increase to both residues. After 236 days in the field, the average dry matter amount left behind in the bags at the different grazing intensities and nitrogen levels were between 20 and 30% to the vegetable residue and between 30 and 50% to the animal residue.